Tandem walking exercise to improve cognitive function in the elderly - I Made Dhita Prianthara; Iga Sri Wahyuni Novianti; I Putu Prisa Jaya; Ni Putu Diah Anantari; Ni Kadek Yuni Fridayani (Jurnal Keolahragaan, 2023)
Decreased cognitive function in the elderly is the leading cause of inability to carry out normal daily activities, as well as a high level of reliance on others in caring for themselves. The many problems that arise due to decreased cognitive function require a healthy aging process so that decreased cognitive function does not cause health problems in the lives of the elderly. Decreased cognitive function in the elderly is the biggest cause of inability to carry out normal daily activities and is also the cause of the elderly experiencing a high level of dependence on others in caring for themselves. The purpose of this study was to determine the effectiveness of tandem walking exercises in improving the cognitive function of the elderly. This research is experimental with a one-group pre and post-test design. Target population in this study were the elderly who experienced cognitive impairment in Dangin Puri Kauh Village, Denpasar Utara District. Sampling method used in this research is purposive sampling. The research sample consisted of 24 people who were given tandem walking exercise. Measurement of cognitive function was carried out using the Mini Mental State Examination (MMSE), which was measured before and after being given training. Data obtained were analyzed using the SPSS Version 25.0 application. The results of testing the hypothesis using the wilcoxon rank test obtained an average before training of 22.46 and an average after training of 27.08 with a value of p = 0.000. From the results of this study, it can be concluded that tandem walking exercises can improve cognitive function in the elderly